Pengaruh Kepemimpinan Terhadap Pola Kerja Pesantren (Studi Kasus di Bidang Perekonomian Pondok Pesantren Sunan Drajat Lamongan) - Yayuk Fauziyatun Nisa; Siswadi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2019)
The leader is one of the essences of management, the main resource and the central point of every activity that occurs in a company. How the creativity and dynamics of a leader in carrying out his leadership authority will greatly determine whether the company's goals can be achieved or not. Leaders who are dynamic and creative, the organization they lead will also be more dynamic and the activities that will be carried out will be more and more. The problems in this study are, 1. How is the leadership style of the head of the economic field of the Islamic boarding school Sunan Drajat Lamongan, 2. Is there any influence of leadership on the economic performance of the employees of the Islamic boarding school Sunan Drajat Lamongan. As for in this study the authors used quantitative data. Research starts from theories or hypotheses using a correlational approach. The results of this study are, 1). The leadership style applied by the head of the economic field of the Islamic boarding school Sunan Drajat Lamongan is a situational style. This is evidenced by the results of interviews and research that has been carried out by researchers. 2). The results of the regression test on the leadership style variable on employee performance in the economic field of the Islamic boarding school Sunan Drajat Lamongan obtained the regression equation Y = 21.740 + 0.464 X. And the results of the hypothesis test obtained a t-test result of 3.168 with a significant level of 0.002. The significant value is less than 0.005 (0.002 < 0.005), thus H0 is rejected and H1 is accepted. So it can be said that there is a positive and significant influence between the influence of leadership style on employee performance.